2021
DOI: 10.2478/joeb-2021-0011
|View full text |Cite
|
Sign up to set email alerts
|

Assessing ischemic injury in human intestine ex vivo with electrical impedance spectroscopy

Abstract: Electrical impedance spectroscopy is a well-established tool for monitoring changes in the electrical properties of tissue. Most tissue and organ types have been investigated in various studies. As for the small intestine, there are several published studies conducted on pig and rat models. This study investigates the changes in passive electrical properties of the complete wall of the human intestine non-invasively during ischemia. We aim to use the passive electrical properties to assess intestinal viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The Cole Model consists of low-frequency resistance ( R 0 ), high-frequency resistance ( R ∞ ), a shape parameter (α) associated with dielectric dispersion, and a time constant ( τ ) [ 30 , 31 ].…”
Section: Bioimpedance For Non-invasive Tissue Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cole Model consists of low-frequency resistance ( R 0 ), high-frequency resistance ( R ∞ ), a shape parameter (α) associated with dielectric dispersion, and a time constant ( τ ) [ 30 , 31 ].…”
Section: Bioimpedance For Non-invasive Tissue Evaluationmentioning
confidence: 99%
“…They found that bioimpedance could provide a quantitative organ assessment that would allow for more accurate pre-transplant clinical decisions. In the recent work of Hou et al [ 30 ], they studied the temporal bioimpedance of resected segments of the highly layered human small intestine. They found that the normalized resistance ((R 0 − R i )/R 0 ) × 100 = P y ) initially decreased and subsequently increased before decreasing over a 10 h period of monitoring.…”
Section: Bioimpedance For Non-invasive Tissue Evaluationmentioning
confidence: 99%
“…Various ways have been proposed for the viability assessment [6][7][8][9][10][11][12][13][14][15]. Most of these ways determine the state of blood circulation in the vessels of bowel walls.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the ways that do not use injections and evaluate the condition of all bowel tissues, and not only the bowel vessels, are more effective [14,16,17]. However, the well-known ways are not widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Strand-Amundsen et al [ 15 ] used bioimpedance measurements together with machine learning algorithms (LSTM-RNN) to more accurately assess intestinal viability in a pig model. Some years later, Hou et al [ 16 ] used bioimpedance measurements on human intestine ex vivo, reporting an association between the value from the bioimpedance data and the viability of the small intestine. Moreover, Hou et al [ 3 ] investigated the use of dielectric relaxation spectroscopy together with machine learning methods (LSTM and CNN) to assess small intestinal viability.…”
Section: Introductionmentioning
confidence: 99%